GRA Lending Toolkit and Conditionality-Reform Proposals. (Policy Papers; Policy Paper ;, 2009)
The Executive Board of the International Monetary Fund (IMF) considered a series of papers to reform the Fund's nonconcessional lending framework. This culminated in the approval of a major overhaul of the IMF's lending framework, including the creation of a new Flexible Credit Line (FCL). The changes to the IMF's lending framework which are described in GRA Lending Toolkit and Conditionality-Reform Proposalsand GRA Lending Toolkit and Conditionality-Reform Proposals-Revised Proposed Decisions include: -- modernizing IMF conditionality for all borrowers, -- introducing a new Flexible Credit Line, -- enhancing the flexibility of the Fund's traditional stand-by arrangement, -- doubling normal access limits for nonconessional resources, -- simplifying cost and maturity structures, and -- eliminating certain seldom-used facilities. The series of papers are: Review of Fund Facilities-Analytical Basis for Fund Lending and Reform Options, Conditionality in fund-Supported Programs-Purposes, Modalities and Options for Reform, Charges and Maturities and Proposals for Reform, Supplement 1 and Supplement 2, Review of Fund Facilities-Analytical Basis for Fund Lending and Reform Options, and Review of Limits on Access to Financing in the Credit Tranches and Under the Extended Fund Facility, and Overall Access Limits Under the General Resources Account provide the background on the earlier discussion of reforms in each of these areas.